Review on automatic text summarization - Rajasekaran, Abirami; R. Varalakshmi, Dr (International Journal of Engineering and Technology, 2018)
Due to the abundant information available in different forms of sources and genres, there is an immense need to summarize the data for humans. Text Summarization has gained more popularity in this fast-growing information age. Past few years have witnessed a rapid growth in the research of summarizing the text automatically using different approaches. This paper provides an in-depth review of the vari-ous approaches, techniques, methods involved in Automatic Text Summarization.Â